Pyogenic spondylodiscitis and osteoradionecrosis of the cervico-thoracic spine: a rare complication after surgery and radiation for hypopharyngeal cancer - Gradoni, Paolo; Oretti, Gabriele; Ferri, Andrea; Ferri, Teore (Acta Biomedica Atenei Parmensis, 2013)
Objective: To describe a rare case of osteoradionecrosis and pyogenic spondylodiscitis of the cervico-thoracic spine after surgery and radiotherapy for hypopharyngeal cancer. Methodology: Diagnostic clues are presented and critically discussed with particular regard to computed tomography, magnetic resonance and positron emission tomography features advising the association between and osteoradionecrosis and spondylodiscitis. Results and Conclusions: Pathogen isolation via CT-guided biopsy provided the definite diagnosis and indicated the targeted therapy. Successful recovery was obtained with conservative treatment.